Creative teaching of physical education for the intermediate fast learners - Nuqui, Josefina M. 1944-; Baldo, Trinidad C. (1973)
The purpose of the study is to help the teachers have a basic understanding and knowledge of some of the creative activities and procedures which can be used in teaching Physical Education to intermediate fast learners. The researcher believes that only through the creative teaching of Physical Education can the intermediate fast learners be physically fit and active, and not disliking physical activities.
Thesis (Master of Arts in Teaching - Special Education : Gifted Sequence)--University of the Philippines, Diliman.
Keywords: Physical education and training -- Philippines; Activity programs in education -- Philippines; Gifted children -- Education -- Philippines; Teaching -- Philippines